Strategi Komunikasi Politik Partai Demokrasi Indonesia Perjuangan (PDI-P) Di DKI Jakarta dalam Menyambut Pemilu 2024 - Gani, Jaidi; Arrianie, Lely; Ambarwati, Ambarwati (Jurnal Komunikasi dan Ilmu Sosial, 2023)
The purpose of this research is to find out how the political communication strategy of the PDI-Perjuangan party in DKI Jakarta—approaching the 2024 election. The theory used is Dan O,Hair's communication strategy theory which includes (1) situational knowledge, (2) overcoming goals, (3) communication competence and (4) anxiety management. Qualitative research method with a case study approach. the results of the study show that: (1) on the situational ignorance of the PDI-Perjuangan DKI Jakarta carry out a political communication strategy through approach efforts by placing its cadres in the electoral district according to the background in their respective regions for candidates for the DPR-RI and provincial, district and city DPRD . (2) Judging from the acquisition of the goal, the communication strategy carried out by the PDI-Perjuangan DKI Jakarta aims is to win the Election in DKI Jakarta by obtaining the most votes in the 2024 election. campaign for teamswithe political communication skills and understand thepeople's charactere in their respective electoral districts. (4) Judging from the anxiety management element, the political communication strategy carried out by the PDIP DKI Jakarta party is by equipping cadres and candidates, witnesses and the campaign team with knowledge about elections and applicable regulations. Regarding the 2024 legislative election, the following includes legislative candidates and cadres of prospective leaders in party political schools. Especially to win the battle in the 2024 election. The conclusions in this study indicate that Dan O'Hair's (2009) strategic communication model will be implemented by the Indonesian Democratic Party of Struggle DKI Jakarta. To prepare for the 2024 general election with a political communication strategy which includes four components, namely; situational knowledge, goal capture, communication competence, and anxiety management and the researchers suggest that the PDI-Perjuangan DKI Jakarta implement this political communication strategy consistently in order to win the 2024 election.